Physicochemical and bioactivity properties of hydroxy apatite coatings electrodeposited onto titanium substrates / Nik Norziehana Che Isa - Che Isa, Nik Norziehana (2013)
Titanium and its alloys have widely been used as metallic implants because of their good biocompatibility and high corrosion resistance. However, they exhibit no bioactive properties and fail to bind to bone tissue. In order to make the titanium implants bioactive, hydroxyapatite (HAp) has been coated onto titanium surface. In this study, HAp coatings were successfully prepared on titanium substrates by electrodeposition technique using aqueous solution containing CaCb + NH4H2PO4 with Ca/P ratio equal to 1.67. The effects of varying deposition conditions and solutions such as applied potential, deposition time, deposition solution concentration and the addition of chitosan into deposition solution on the electrodeposition process as well as the formation of HAp coatings were investigated. The obtained deposited HAp samples were characterized using FESEM, EDAX, XRD, FTIR, immersion in SBF solution and Scotch® tape test. The deposition conditions and solutions have strongly affected the formation of HAp coatings. The best HAp coating was produced by applying a constant potential o f - 1.5 V vs Ag/AgCl using 0.167 M CaC^ + 0.1 M NH4H2PO4 solution at 80 °C for 30 min. The addition of 5 volume percent of chitosan into the deposition solution has improved the adhesion of HAp coatings on the Ti surface. It was found that the prepared HAp coatings are bioactive as shown by the change of surface morphology after immersion in SBF solution for a few days. The HAp material can also be deposited on different types of Ti substrates (i.e.: Ti mesh and NiTi alloy) using the electrodeposition technique. It was also proven that coated HAp onto Ti substrates gave better physicochemical properties of Ti implants.